Carotid artery stenosis: current and emerging treatments - Chaturvedi, Seemant; Rothwell, Peter (Neurological disease and therapy, 2005)
1.Introduction /Peter M. Rothwell and Seemant Chaturvedi --2.Epidemiology of carotid artery stenosis /Robert Cote and Jeffrey Minuk --3.Pathophysiology /Hugh Markus --4.Carotid imaging -- is angiography still needed? /David Pelz --5.Carotid imaging : use of ultrasound /Michael G. Hennerici and Michael Daffertshofer --6.Antithrombotic therapy for carotid artery stenosis /Seemant Chaturvedi --7.Stroke prevention, blood cholesterol, and statins /Pierre Amarenco, Philippa Lavallee and Pierre-Jean Touboul --8.Management of hypertension in carotid stenosis /J. David Spence --9.Hyperhomocyst(e)inemia and carotid atherosclerosis /Houta S. Sabet and L. Creed Pettigrew --10.Diet in the management of patients with carotid stenosis /J. David Spence --11.Angiogenesis and angiogenic growth factors as future therapies for cerebrovascular disease /Brian H. Annex and Christopher D. Kontos --12.What are the current operative risks of carotid endarterectomy? /Peter M. Rothwell --13.Benefits of endarterectomy for recently symptomatic carotid stenosis /Peter M. Rothwell --14.Management of carotid artery disease : carotid endarterectomy for asymptomatic carotid stenosis /Graeme J. Hankey --15.Surgical controversies /A. Ross Naylor --16.Symptomatic carotid artery occlusion : extracranial intracranial bypass and other treatment options /Catharina J. M. Klijn and L. Jaap Kappelle --17.Stenting for symptomatic stenosis /Lucy Coward and Martin M. Brown --18.Stenting for asymptomatic stenosis /Mark K. Borsody and Seemant Chaturvedi --19.Angioplasty and stenting for non-atherosclerotic diseases of the carotid artery /Kumar Rajamani and Seemant Chaturvedi --20.Controversies in endovascular therapy for carotid artery stenosis /Andrew R. Xavier, Catalina C. Ionita, Jawaad F. Kirmani and Adnan I. Qureshi.
Includes bibliographical references and index